Bioprostheses and Mechanical Prostheses for Aortic Valve Replacement in Patients Aged 50 to 65 Years Offer Similar Long-Term Survival Rates - Toporcer, Tomáš; Lukačín, Štefan; Kraus, Andrea; Homola, Marián; Bereš, Anton; Trebišovský, Michal; Radótzy, Denis; Rohn, Vilém; Kolesár, Adrián (Journal of cardiovascular development and disease, 2025)
BACKGROUND: Aortic valve replacement (AVR) is the definitive therapy for patients with severe aortic valve stenosis (AoS). The aim of this work is to compare the effect of a mechanical prosthesis (MP) and a bioprosthesis (BP) on the survival of patients aged 50-65 years after AVR. METHODS: The retrospective analysis included 276 patients aged 50 to 65 years who had undergone isolated AVR for AoS; 161 patients were implanted with an MP and 115 with a BP. Patient survival, adjusted for age, gender and risk parameters affecting survival, was assessed. A subgroup analysis was performed on the 208 patients with a modern valve (prosthesis models that are no longer used in clinical practice were removed from the sample). RESULTS: After adjusting for risk factors for overall survival as well as for age and sex, the implantation of an MP did not have a significant effect on overall survival in comparison to a BP, at a median follow-up of 10.3 years (p = 0.477). The size of the MP had no significant effect on overall survival either (HR: 1.29; 95%CI: 0.16-10.21; p = 0.812). However, the indexed effective orifice area of the BP had a positive effect on overall survival (HR: 0.09; 95%CI: 0.01-0.78; p = 0.029). CONCLUSIONS: The estimated survival of patients aged between 50 and 65 years after implantation of a BP with a sufficiently large indexed effective orifice area may exceed that of patients with an MP.
Keywords: aortic valve replacement; mechanical prosthesis; bioprosthesis; aortic valve stenosis